2009
DOI: 10.1111/j.1460-9568.2009.06864.x
|View full text |Cite
|
Sign up to set email alerts
|

Prior intention can locally tune inhibitory processes in the primary motor cortex: direct evidence from combined TMS‐EEG

Abstract: Human subjects are able to prepare cognitively to resist an involuntary movement evoked by a suprathreshold transcranial magnetic stimulation (TMS) applied over the primary motor cortex (M1) by anticipatory selective modulation of corticospinal excitability. Uncovering how the sensorimotor cortical network is involved in this process could reveal directly how a prior intention can tune the intrinsic dynamics of M1 before any peripheral intervention. Here, we used combined TMS-EEG to study the cortical integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 47 publications
(82 reference statements)
5
52
0
1
Order By: Relevance
“…TMS-evoked N100 occurred already at subthreshold TMS intensities with highly reliable amplitudes (Bender et al, 2005a). This supports previous evidence that TMS-evoked N100 adds additional and independent information to measures based on MEP amplitudes and may be a marker of cortical inhibition (Bender et al, 2005a;Bonnard et al, 2009;Ilmoniemi et al, 2010). We found that less TMS-evoked N100 reduction (i.e.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…TMS-evoked N100 occurred already at subthreshold TMS intensities with highly reliable amplitudes (Bender et al, 2005a). This supports previous evidence that TMS-evoked N100 adds additional and independent information to measures based on MEP amplitudes and may be a marker of cortical inhibition (Bender et al, 2005a;Bonnard et al, 2009;Ilmoniemi et al, 2010). We found that less TMS-evoked N100 reduction (i.e.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast to MEPs, which are potentially affected by a combination of cortical, subcortical and spinal mechanisms (Kiers et al, 1993), the TMS-evoked N100 directly assesses cortical responses to TMS without influences of spinal inhibitory mechanisms (Nikulin et al, 2003;Bender et al, 2005a;Ilmoniemi and Kicic, 2010). In healthy subjects, the TMS-evoked N100 component decreases during motor cortex disinhibition related to movement execution (Nikulin et al, 2003) and motor response preparation (Bender et al, 2005a) and increases during response inhibition (Bonnard et al, 2009). Therefore, the TMS-evoked N100 is considered to be a marker of motor cortex inhibition influenced by cortico-striato-thalamo-cortical loops (Bender et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to SP duration, our findings demonstrate that LICI in young subjects was greater during both shortening and lengthening contractions, suggesting increased GABAB mediated inhibition within M1 during movement in healthy young subjects. This increase in LICI is consistent with a previous report that the EEG derived N100 response is greater during movement preparation in young subjects [48]. Despite this, LICI in old subjects was unaffected by contraction type, suggesting that the ageing process results in reduced modulation of intracortical GABAB-mediated circuitry during movement.…”
Section: Changes In Lici and The Sp During Anisometric Contractionssupporting
confidence: 81%
“…Converging evidence from several studies, however, shows that direct effects of TMS to the N100-P200 are substantial, probably more important than sensory stimulation. 19,25,26,33,34 The N100 is sensitive to certain clinical conditions, including ADHD 35 and mild cognitive impairment, 27 where reduced N100 amplitudes have been found. The balance of cortical inhibitory and facilitatory circuits in paired-pulse TMS-EEG is also reflected in latencies.…”
Section: Introductionmentioning
confidence: 99%